(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kachalova T.H. Conceptual bases of problem of formation of social activity of students (didactic aspect). In the article on the basis of analysis of researches of philosophical, psychological and pedagogical literature specified concepts «socialization», «social activity», the circle of theoretical questions is outlined in relation to forming of social activity of student, the role of sociuma is determined in forming of active social position of personality.